CD8+and Regulatory T cells Differentiate Tumor Immune Phenotypes and Predict Survival in Locally Advanced Head and Neck Cancer - Echarti, Alessia; Hecht, Markus; Büttner-Herold, Maike; Haderlein, Marlen; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Cancers, 2019)
Background: The tumor immune status "inflamed", "immune excluded", and "desert" might serve as a predictive parameter. We studied these three cancer immune phenotypes while using a simple immunohistochemical algorithm. Methods: Pre-treatment tissue samples of 280 patients with locally advanced HNSCC treated with radiochemotherapy were analyzed. A double staining of CD8+ cytotoxic T cells (CTL) and FoxP3+ (Treg) was performed and the cell density was evaluated in the intraepithelial and stromal compartment of the tumor. Results: The classification of tumors as "immune desert" when stromal CTL were <= 50 cells/mm(2), "inflamed" when intraepithelial CTL were > 500 cells/mm(2), and as "excluded" when neither of these definitions met these cut off values allowed the best discrimination regarding overall survival. These groups had median OS periods of 37, 61, and 85 months, respectively. In "immune desert" and "immune excluded" tumors high Treg tended to worsen OS, but in "inflamed" tumors high Treg clearly improved OS. Conclusions: We propose that, in locally advanced HNSCC, the tumor immune state "inflamed", "immune excluded", and "immune desert" can be defined by intraepithelial and stromal CTL. Tregs can further subdivide these groups. The opposing effects of Tregs in the different groups might be the reason for the inconsistency of Tregs prognostic values published earlier.
CRIS-Team WoS Importer:2019-10-25